Relatório de Estágio Profissional "Aprender a Ensinar e Ensinar para Aprender" - Cristiana Sofia de Almeida Baptista (2017)
This document comes within the scope of the Professional Internship course, inserted in the 2nd cycle of studies related to the Master's degree in Physical Education Teaching in Basic and Secondary Education. The Professional Internship took place in a school in the Porto, in a nucleus made up of three student-trainees, a cooperating teacher of the institution and a professor of the Faculty of Sport of the University of Porto. My pedagogical practice focused on the teaching of physical education classes and theoretical classes of practices of physical and sport activities to a group of 10º year and the accompaniment of the school sport to children of the 1º cycle. The construction of this report was based on the experiences experienced during the school year, which contributed to the construction of my professional identity.It was structured in six chapters: the first, "introduction," frames the document and portrays its purpose; In the second "Personal Dimension" is carried out an autobiography and expectations for the stage; In the third "Framework of professional practice", a legal, institutional and functional characterization of professional practice is carried out; In the fourth chapter "Realization of the professional practice" an account is made of the work developed during the professional stage supported in three large areas, being Area 1 - Organization and Management of Teaching and Learning, area 2 - Participation in school and relationship with community and area 3 - Professional development; The fifth chapter concerns the research-action study, "Dilemmas and difficulties of the student-trainee in the course of the professional stage: Study focused on the emission of feedback (s) during the class activities"; In the last chapter on "Conclusions" an analysis is made of all the work carried out throughout the year. This document mirrors my experience, as a student-trainee, in the professional stage, through a conscious and responsible reflection of my training process as a physical education teacher.